Wielomian w(x) = -2x^4 +ax^2 +2x -4 spełnia warunek w(√2) = -w(-√2). Wynika stąd że:.



Odpowiedź :

[tex]w(x)=-2x^4+ax^2+2x-4\\w(\sqrt2)=-w(-\sqrt2)[/tex]

[tex]w(\sqrt2)=-2*(\sqrt2)^4+a*(\sqrt2)^2+2\sqrt2-4\\w(\sqrt2)=-8+2a+2\sqrt2-4\\w(\sqrt2)=2a+2\sqrt2-12[/tex]

[tex]-w(-\sqrt2)=-(-2*(-\sqrt2)^4+a*(-\sqrt2)^2+2*(-\sqrt2)-4)\\-w(-\sqrt2)=-(-8+2a-2\sqrt2-4)\\-w(-\sqrt2)=-(2a-2\sqrt2-12)\\-w(-\sqrt2)=-2a+2\sqrt2+12[/tex]

[tex]2a+2\sqrt2-12=-2a+2\sqrt2+12\\2a+2a=12+12\\4a=24 /:4\\\fbox{a=6}[/tex]